Nurse induced respiratory depression by succinylcholine – the 'hero syndrome'. Issue 9 (15th May 2013) - Musshoff, F.; Kuepper, U.; Madea, B.
Abstract : A nurse administered the neuromuscular blocking agent succinylcholine (SUX) to at least one patient and gave first aid in the therapy of unexpected respiratory depression. SUX is regarded as an undetectable and thus perfect poison due to its short half‐life and degradation to the endogenous compounds choline and succinic acid. However, SUX and especially its metabolite succinylmonocholine (SMC) were found in plasma and urine a few hours after administration by means of high performance liquid chromatography‐tandem mass spectrometry (HPLC‐MS/MS). Compared to clinical studies, the window of detection was sufficient to gain definite proof; in other cases no samples were collected. The nurse enjoyed high reputation with the doctors. According to the court she wanted to present herself spectacularly as the first and decisive rescuer to demonstrate her special abilities and capacities, perhaps to receive a better job in the hospital. Considering the actual case, the hero syndrome is not limited to fire‐fighters. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A nurse administered succinylcholine (SUX) and gave first aid in the therapy of unexpected respiratory depression. SUX and succinylmonocholine (SMC) were found in plasma and urine. She wanted to present herself spectacularly as the first and decisive rescuer.